Outcomes and Characteristics of Patients Receiving Second-line Therapy for Advanced Pancreatic Cancer. (February 2019) - Tsang, Erica S.; Wong, Hui-li; Wang, Ying; Renouf, Daniel J.; Cheung, Winson Y.; Lim, Howard J.; Gill, Sharlene; Loree, Jonathan M.; Kennecke, Hagen F.
Abstract : Objectives: There is limited randomized data to guide second-line chemotherapy selection in advanced pancreatic cancer (APC). We aimed to characterize predictors and outcomes of second-line chemotherapy in patients with APC. Methods: We identified all patients with APC [locally advanced (LAPC) or metastatic (MPC)] who received ≥1 cycle of first-line chemotherapy between January 2012 and December 2015 across 6 cancer centers in British Columbia, Canada. Baseline characteristics and survival outcomes were summarized. Results: Of 676 patients with APC (31% LAPC, 69% MPC) who received ≥1 cycle of chemotherapy, 164 (24%) received second-line chemotherapy. These patients were younger, with lower ECOG and higher CA19-9 at presentation, compared with patients who did not receive second-line chemotherapy. There were no differences in rates of second-line chemotherapy between LAPC and MPC (28% vs. 23%; P =0.18). Only first-line FOLFIRINOX was associated with second-line chemotherapy. Median overall survival (OS) from second-line chemotherapy was longer with second-line gemcitabine/nab-paclitaxel than fluoropyrimidine or gemcitabine (7.9 vs. 5.1 vs. 4.3 mo; P =0.008). On multivariable analysis, longer OS from second-line chemotherapy was associated with gemcitabine/nab-paclitaxel, lower ECOG, and LAPC. Conclusions: In this population-based cohort, first-line FOLFIRINOX was the strongest predictor of second-line chemotherapy. Duration of therapy remains short and novel treatments are urgently needed.